Sanctifying the House: Child Burial in Prehistoric Anatolia - Yıldırım, Burcu (Near Eastern archaeology, 2018)
Intramural burials are common on the Anatolian plateau, beginning in early prehistory. Neolithic examples indicate that the incorporation of human remains into domestic architecture was a regular part of the rhythm of family life. By the Late Chalcolithic, adult burials have largely moved into extramural cemeteries, although there are some exceptions. Infants and small children, however, continue to be buried within the house and these interments are a common feature on the Anatolian plateau. At the site of Çadır Höyük in central Anatolia, well over one dozen Chalcolithic infant burials were placed in corners of existing rooms, in areas of possible ritual function, and incorporated in walls at the time of construction. This study investigates the relationship between the spatial context of these burials and their function in the domestic context, and considers the possibility that some infant burials served as foundation deposits in the architecture at Chalcolithic Çadır.